Re-instatement of Craterostigma nanum (Linderniaceae) from the Pondoland Centre of Floristic Endemism and key to the South African species - Grieve, Katharine W.; Bester, Stoffel P. (Phytotaxa, 2023)
There are currently only two species of Craterostigma recognised for South Africa, C. plantagineum and C. wilmsii. The present paper deals with the Craterostigma plants from the Pondoland Centre of Floristic Endemism along the eastern coast of South Africa. It is presently a synonym of C. plantagineum, an inland species of high elevations. However there are differences between C. plantagineum and the Pondoland plants, and a case is made for the re-instatement of C. nanum for the latter. An expanded description is provided, along with a proposed conservation assessment, and key to the species in South Africa.